Labour Exploitation and Work-Based Harm - Scott, Sam (2017)
Labour exploitation is a highly topical though complex issue that has international resonance for those concerned with social justice and social welfare, but there is a lack of research available about it. This book, part of the Studies in Social Harm series, is the first to look at labour exploitation from a social harm perspective, arguing that, as a global social problem, it should be located within the broader study of work-based harm. Written by an expert in policy orientated research, he critiques existing approaches to the study of workplace exploitation, abuse and forced labour. Mapping out a new sub-discipline, this innovative book aims to shift power from employers to workers to reduce levels of labour exploitation and work-based harm. It is relevant to academics from many fields as well as legislators, policy makers, politicians, employers, union officials, activists and consumers.